FISCHEE.-TROPSCH SYNTHESIS OVER RUTHENIUM PROMOTED COBALT CATALYSTS - YAKUBOV, ADKHAM (2012)
Gas-to-Liquid (GTL), in particular Fisher-Tropsch synthesis (FTS) is a process of converting coal, natural gas and biomass derived synthesis gas into transportable liquid fuels. Depleting resources of crude oil and a growing demand for alternative sources of energy has encouraged renewed interest in the development of efficient GTL technology for clean fuel production via FTS. In this study autoclave type stirred reactor was used and utilized in semi batch regime. Multiwall carbon nanotubes (MWCNT) were commercially obtained and "treated with concentrated nitric acid and further dried overnight at 120°C and calcined at 300°C. Another support material which is SBA-15 was synthesized using Pluronic P123 and Tetraethyl orthosilicate (TEOS). These supports were used to synthesize lwt%Ru/10-30wt%Co/MWCNT and lwt%Ru/10-30wt%Co/SBA-15 catalysts were prepared by incipient wetness impregnation. In addition 10wt%Co/MWCNT and 10wt%Co/SBA-15 were prepared as a reference catalysts in order to study the effect of ruthenium promoter. All catalysts and support materials were characterized by field emission scanning electron microscope (FESEM) equipped with energy dispersive X-ray spectroscopy (EDX), surface area analyzer, X-ray diffractometer (XRD), Transmission Electron Microscope (TEM)and temperature-programmed reduction (TPR).Co(N03)2#6H20 was used as a cobalt precursor and ruthenium (III) acetylacetonate ((C5H702)3Ru) as ruthenium precursor. FT synthesis was carried out in slurry phase environment where catalysts were suspended in high boiling point solvent n-hexadecane. Commercial parameters were used, that is 220°C, 20 bar and H2/CO feed gas ratio of 2. Experimental results revealed that the yield of C8+ HC was higher when SBA-15 was used as support comparing to MWCNT due to the high surface area higher pore volume and pore size. High pore volume allows high loading of cobalt metal. In addition, it provides high dispersion of cobalt along the surface and enhancement of active sites of the catalyst which contributes tohigher conversion ofsynthesis gas to valuable products. Addition ofruthenium oxide did not make significant contribution to product yield, but positively affected the catalyst reduction temperature and metal particle size dispersion on MWCNT.